Serum Galectin-3 Level in Patients with Scleroderma. - Ozgen, Metin; Koca, Suleyman Serdar; Akbas, Fatma; Ilhan, Nevin; Gundogdu, Baris; Isik, Ahmet (Wiley, 2011)
[Abstract Not Available]
75th Annual Scientific Meeting of the American-College-of-Rheumatology (ACR) / 46th Annual Scientific Meeting of the Association-of-Rheumatology-Health-Professionals (ARHP) -- NOV 04-09, 2011 -- Chicago, IL